Comparative Study of the Ecotoxicological and Histopathological Impacts of Effluent, Sludge Water, and Commonly Used Inorganic Fertilizers on Juvenile Oreochromis niloticus (Linnaeus, 1758) - Guzman, Maria Aileen Leah G.; Espiritu, Emilyn Q.; Unson, Jewel Racquel; Alba, Vince Jethro; Sy, Lara Anne; Hernandez, Maria Larisse; Dumo, Joan Ruby; Espinas, Jay Roy (2019)
Wastewater treatment systems, designed to treat domestic wastes, produce effluents and sludge that are high in organic matter and nutrient content. These effluents and sludge are now being used as organic fertilizers because such nutrients and organic matter are vital to plant growth. However, without proper treatment, these substances may eventually find their way into bodies of water through run off and/or infiltration with potentially dangerous consequences. This study, therefore, investigated the potential toxic effects of effluents and sludge produced from wastewater treatment facilities against commonly used inorganic fertilizers to an aquatic species. Toxicity tests (expressed as mean 96-hr LC50 in mg/L) and histopathological examinations of the liver were conducted using juvenile Oreochromis niloticus (Linnaeus, 1758) exposed to varying concentrations of effluent, sludge, and inorganic fertilizers (i.e., urea and complete fertilizer) to assess both acute and sublethal effects. The results of the acute toxicity tests show concentrations (expressed as mean 96-hr LC50 in mg/L or ppm) arranged in decreasing order of toxicity to tilapia: complete fertilizer 14-14-14 (1,396 ppm) > urea (16,152 ppm) > sludge (145,900 ppm) > effluent (465,000 ppm). Histopathological examinations of liver tissues showed that exposure to the two inorganic fertilizers resulted to blood congestion and degeneration in comparison to those exposed to the sludge. Furthermore, results for fishes exposed to the lowest concentrations of the effluent also showed alterations in the liver tissue. These results demonstrate that the sludge and effluent are less toxic by several orders of magnitude than the inorganic fertilizers. It is suggested that further chronic toxicity and histopathological studies be done to determine their long-term impacts to receiving aquatic organisms to establish their potential for agricultural applications.
Keywords: Fertilizers; Wastewater treatment